The effects of blanching and sulfiting on the color, flavor and texture of candied langka (Arthocarpus integrifolia) - Minoza, Miraflor A.; de la Paz, Sylvia (1959)
(NO ABSTRACT PROVIDED BY THE AUTHOR)
Thesis (BSFT)--University of the Philippines Diliman
Keywords: Candied fruit -- Philippines